Nanoparticles assembled from mixtures of whey protein isolate and soluble soybean polysaccharides. Structure, interfacial behavior and application on emulsions subjected to freeze-thawing - Cabezas, Dario Marcelino (2019)
In this article, the freeze-thaw stability of emulsions prepared with nanoparticles assembled from mixtures of whey protein isolate (WPI, 2.0% w/w)and soluble soybean polysaccharides (SSPS, 0.5% w/w)was assessed. The assembly was performed by pH adjustment to 3.0 without and with heating (90 °C, 15 min). Moreover, the order of addition of SSPS to proteins, before or after heating, was also studied. The complexes were characterized by dynamic light scattering, turbidity, non-sedimentable protein content, aromatic surface hydrophobicity (H 0 ), interfacial tension and interfacial rheology measurements at the oil/water interface. In all cases, the dispersions evidenced slightly-positive ζ-potential values due to electrostatic associative interactions between proteins and SSPS. Moreover, the complexation increased the particle size, the interfacial activity and the non-sedimentable protein content. Oil-in-water emulsions (30% w/w sunflower oil)prepared with unheated WPI/SSPS mixtures were more stable to freeze-thawing (−18 °C, 72 h; 20 °C, 2 h)respect to those prepared with WPI alone. When SSPS was added to previously heated proteins, the resultant emulsions also evidenced a high freeze-thaw stability. The large sedimentable species, which contributed to form a film of high viscoelasticity, could stabilize the emulsions by a Pickering mechanism. However, when SSPS and WPI were heated together, the resultant emulsions exhibited a low freeze-thaw stability due to a combination of poor emulsification ability and limited interfacial adsorption of large particles. The results of this article might have important implications in the preparation of highly acidic emulsion-based products resistant to freeze-thaw treatments.